Congratulations Puan Durrani Aimi Abdul Malik for Passing her VIVA VOCE - Yuhani, Yusof (2022)
On behalf of the Centre for Mathematical Sciences, we would like to congratulate Puan Durrani Aimi binti Abdul Malik, Master of Science (NEC461) – Field of Research in Mathematics, under the supervision of Assoc. Prof. Dr. Yuhani binti Yusof and co-supervised by Dr. Ku Muhammad Na`im bin Ku Khalif for successfully passing her viva voce on 21st October 2022. The title of her thesis is “Hybrid Fuzzy Analytical Process with Fuzzy Inference System on Ranking STEM Approach towards Blended Learning in Mathematics”.